Serological and Molecular Diagnosis of Human Cytomegalovirus among Hemodialysis Patients in Kirkuk/Iraq - Eman Ammar Ihsan; Lezan Medhat Mohammed; Waleed Mohammed Ali (Medical Journal of Babylon)
Background: Cytomegalovirus (CMV) is a common herpes virus and is usually asymptomatic in healthy individuals. CMV has a worldwide distribution, infecting about 40% to 90% of adults, leading to lifelong latent infection. Hemodialysis patients’ weakened immune systems have long been known to contribute to greater prevalence rates of viral infections like CMV. Objectives: The purpose of the current study was to estimate the rate of prevalence of human CMV among patients with hemodialysis and also to detect CMV in its acute phase. Materials and Methods: About 50 men and 41 women, all receiving hemodialysis treatment at Kirkuk General Hospital and 50 apparently healthy individuals as the control group, were included in the current study. This study was carried out during the period November 2022 to March 2023. Participants’ sera were examined for the presence of CMV-IgM and CMV-IgG antibodies, as well as DNA by real-time polymerase chain reaction (PCR). Results: While CMV-IgM was only discovered in 5.5% of hemodialysis patients, CMV-IgG was found in 50.5% of them. Only 4% of hemodialysis patients had CMV DNA found. In contrast to females, males had a higher likelihood of having CMV-IgM (60% vs. 40%) and CMV-IgG (55.7% vs. 32.7%, respectively). The highest CMV prevalence was found in older patients, which is related to their weakened immune systems. Conclusion: Detection and prevalence of CMV IgG was greater in HD patients than that of CMV IgM. Patients exposed to CMV during dialysis may cause virus reactivation by immunosuppression and inflammation, suggesting that screening patients is necessary to avoid complications like kidney transplant rejection. As a result, PCR can detect extremely small amounts of DNA, it has a high detection rate in the early stages of CMV infection.